APLIKASI TAPIS PELEWAT RENDAH LC (LOW PASS LC FILTER) UNTUK MEREDUKSI DISTORSI HARMONISA PADA LAMPU HEMAT ENERGI - Sasmoko, Priyo; Subali, Subali; Yuwono, Teguh (Gema Teknologi, 2012)
Priyo Sasmoko, Subali, Teguh Yuwono, in this paper explain that harmonic (current or voltage) is one of the problems that has to be solved in electric power system, especially that caused by non-linear loads. Harmonic could cause bad impacts for the electric components that sensed it. It is almost certain that using of fluorescent lamp with electronic ballast or it is called energy saving lamp can cause harmonic in electric power system. Considering of the using of energy saving lamp is increased fairly fast as residence and office lighting, so it is important to analyze and solve the harmonic that caused by energy saving lamp. From the harmonic analysis, we can know the harmonic distortion caused by energy saving lamp. And there are some efforts to reduce such harmonic distortion by using a Low Pass Filter. Keyword: power quality, harmonic, low pass filter.